Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1051/0004-6361/201016110
|View full text |Cite
|
Sign up to set email alerts
|

Zooming into the broad line region of the gravitationally lensed quasar QSO 2237 + 0305  ≡  the Einstein Cross

Abstract: Aims. We aim to use microlensing taking place in the lensed quasar QSO 2237+0305 to study the structure of the broad line region (BLR) and measure the size of the region emitting the C iv and C iii] lines. Methods. Based on 39 spectrophotometric monitoring data points obtained between Oct. 2004 and Dec. 2007, we derived lightcurves for the C iv and C iii] emission lines. We used three different techniques to analyse the microlensing signal. Different components of the lines (narrow, broad, and very broad) were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
114
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 111 publications
12
114
0
Order By: Relevance
“…However, studies of high-magnification events are likely biased toward small quasar size estimates because it is easier to obtain high magnifications with small sources (e.g., Kochanek 2004;Eigenbrod et al 2008;Blackburne et al 2011). It is also interesting to note that without considering any velocity prior (i.e., adopting a uniform prior), the size determinations of Eigenbrod et al (2008) and Anguita et al (2008) increase by a factor ∼4 (see Sluse et al 2011) but would then require cosmologically unrealistic peculiar velocities for the lens/source.…”
Section: The Observed Magnitude Of Image I=(a B C D) Ismentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies of high-magnification events are likely biased toward small quasar size estimates because it is easier to obtain high magnifications with small sources (e.g., Kochanek 2004;Eigenbrod et al 2008;Blackburne et al 2011). It is also interesting to note that without considering any velocity prior (i.e., adopting a uniform prior), the size determinations of Eigenbrod et al (2008) and Anguita et al (2008) increase by a factor ∼4 (see Sluse et al 2011) but would then require cosmologically unrealistic peculiar velocities for the lens/source.…”
Section: The Observed Magnitude Of Image I=(a B C D) Ismentioning
confidence: 99%
“…Gravitational microlensing (Chang & Refsdal 1979, 1984; see also Kochanek 2004 andWambsganss 2006) is the main tool used to estimate both parameters, either from time variability or through the wavelength dependence of the microlensing magnification. Microlensing studies (see e.g., Pooley et al 2007;Morgan et al 2010;Blackburne et al 2011Blackburne et al , 2014Blackburne et al , 2015Sluse et al 2011;Jiménez-Vicente et al 2012Hainline et al 2013;Mosquera et al 2013;MacLeod et al 2015) have found that the mean sizes of quasar accretion disks are roughly a factor of 2-3 greater than the predictions of the standard thin disk model. These differences are too large to be explained by contamination from the broad emission lines and the pseudo-continuum contributions, or scattering on scales larger than the accretion disk (Dai et al 2010;Morgan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Reverberation mapping establishes the relationship between the size and the luminosity of the BLR and yields a typical BLR size of RBLR ∼ 0.2 pc (Kaspi et al 2007; Chelouche & Daniel 2012) for high redshift luminous quasars. Differential microlensing allows for a constraint on the accretion disk size < ∼ 3 × 10 −3 pc (Blackburne et al 2011;Jiménez-Vicente et al 2012) and for an estimation of the size of the BLR ∼ 0.1 pc (Sluse et al 2011). The observations of gamma-ray emission constrain the size of a jet constituent to a few parsecs (Abdo et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…6 we show the C iii] profiles for A and B. For the A image, the signal strength is enough to fairly appreciate the expected C iii] asymmetry, with a blue-wing excess due to Al iii (λ1857) and Si iii] (λ1892) emissions (e.g., Sluse et al 2011). The line flux of A is significantly higher than the line flux of B, but the flux ratio B/A is higher than 1 in both continuum zones around the line profiles (see Fig.…”
Section: Spectroscopic Redshift Of the Main Lensing Galaxymentioning
confidence: 99%
“…2.2, and each of these three emissions is most likely generated in spatially different regions (e.g., Marziani et al 2010;Sluse et al 2011;Motta et al 2012). According to Motta et al (2012), the broad wings of a given emission line could be produced in a compact region, whereas its core is probably dominated by photons arising from the NLR and the outer parts of the BLR.…”
Section: Spectroscopic Redshift Of the Main Lensing Galaxymentioning
confidence: 99%